Developing a Conceptual Framework UTAUT-TTF-TOE Model to Examine AI’s Influence on HR Performance in Higher Education - Luomou; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok; Kamales, Nayika (My University, 2026)
The swift advancement of artificial intelligence (AI) is exerting a profound influence on the operational paradigm of higher education, yet the degree of its implementation exhibits substantial disparities among institutions. Presently, there is a dearth of systematic research on the moderating mechanisms of AI adoption intensity on organizational performance. This research integrates the Unified Theory of Acceptance and Use of Technology (UTAUT), task-technology fit (TTF), and the technology-organization-environment (TOE) framework to formulate a comprehensive model for exploring the mechanisms through which AI impacts human resource performance in universities. The research centers on analyzing how technological, organizational, and environmental factors interact to affect AI adoption, specifically investigating the moderating function of adoption intensity in this relationship. This research endeavors to uncover the specific pathways and boundary conditions for AI to improve university management efficiency.
Keywords: Adoption intensity; Artificial intelligence; Higher education; UTAUT-TTF-TOE integrated model